2021
DOI: 10.21203/rs.3.rs-342976/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Steel slag quality control for road construction aggregates and its environmental impact: Case study of Vietnamese steel industry – Leaching of heavy metals from steel making slag

Abstract: Steel slag is an industrial by product of steel manufacturing processes and has been widely used in countries like Japan, United States, and European Union nations. However, the current utilization of steel slag in Vietnam is very low mainly because of lack of quality control of slag treatment and chances for reuse of treated steel slag. This paper presents the current steel slag production status and its potential to use as road construction aggregates in consideration of environmental and quality control iss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…This previous work showed that steel slag and gravel aggregates have a prospective to be used in hot mix asphalt concrete paving mixture [10]. The different testing also conducted in Vietnam to know steel slag potential as road construction [11]. The previous work shows that slag has a potential to be used in road pavement.…”
Section: Introductionmentioning
confidence: 99%
“…This previous work showed that steel slag and gravel aggregates have a prospective to be used in hot mix asphalt concrete paving mixture [10]. The different testing also conducted in Vietnam to know steel slag potential as road construction [11]. The previous work shows that slag has a potential to be used in road pavement.…”
Section: Introductionmentioning
confidence: 99%